2004
DOI: 10.1590/s1516-35982004000400013
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da idade dos frangos de corte sobre a atividade enzimática e digestibilidade dos nutrientes do farelo de soja e da soja integral

Abstract: RESUMO -Esse trabalho visou investigar o efeito da idade de aves sobre a digestibilidade dos nutrientes da soja integral extrusada (SIE), soja integral tostada à vapor (SITV) e farelo de soja com óleo (FSO) na produção de enzimas digestivas do pâncreas. Cinco ensaios de digestibilidade foram conduzidos com frangos de corte de uma, duas, três, quatro e seis semanas de idade. Foi utilizada a metodologia de coleta total de excretas. A atividade das enzimas amilase e tripsina pancreática aumentou linearmente com a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
16

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
4
13
0
16
Order By: Relevance
“…Freitas et al (2005) relate DCEE with the production of pancreatic lipase and bile, explaining that lower DCEE in chickens in relation to roosters may be due to the lower lipase production in young chickens. Sakomura et al (2004) mention that they also observed a positive correlation between the digestibility of ethereal extract of soybean and lipase activity, corroborating the findings in this study. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Freitas et al (2005) relate DCEE with the production of pancreatic lipase and bile, explaining that lower DCEE in chickens in relation to roosters may be due to the lower lipase production in young chickens. Sakomura et al (2004) mention that they also observed a positive correlation between the digestibility of ethereal extract of soybean and lipase activity, corroborating the findings in this study. …”
Section: Resultssupporting
confidence: 91%
“…This behavior supports the hypothesis that chickens modulate enzyme production in a specific way, according to the amount of substrate in the gastrointestinal tract instead of keeping the enzyme activity constantly high (Pinheiro et al, 2004). Sakomura et al (2004) described that the extrusion process of whole soybean increased the lipase activity of broiler chickens in the fourth week of age due to the greater oil exposure caused by the process. According to Rodwell (1990) probably in consequence of the pancreas maturation, a phenomenon that occurs in the organs of the digestive system of birds with time, until the organs reach full development to meet all the physiological needs.…”
Section: Resultsmentioning
confidence: 99%
“…With the advancing age, the gross energy metabolizability coefficient and the ME values of tomato waste increased, which means that the tomato waste can be better used after the initial stage. This has probably occurred because, as the broilers age, their pancreas develop and the digestive enzymes production increases, thus improving the digestion capability and the food energy utilization (Sakomura et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In a research study on the evaluation of enzyme activity and digestibility of nutrients, Sakomura et al (2004) concluded that the maximal allometric growth of the pancreas coincided with the greatest increase in the production of the digestive endogenous enzymes, which, according to Viana et al (2009), is induced by the addittion of enzyme complexes in the diet. In another experiment, conducted by Arija et al (2006), the authors verified that the weights of the digestive organs, intestine and accessory organs and the intestinal viscosity were altered because of the inclusion of extruded beans in the diet of chicks in relation to those fed normal diets based on corn and soybean.…”
Section: Discussionmentioning
confidence: 99%